High-temperature selective catalytic reduction of NO with NH3: Optimization of ZrO2 and WO3 complex oxides. (15th February 2022) - Ge, Zhanzhi; Shen, Yuesong; Gu, Sasa
Graphical abstract: Highlights: ZrO2 -WO3 was active for NH3 -SCR of NO at high temperatures. Deep contact and strong interaction of ZrO2 and WO3 can improve NO reduction. Lewis acid sites play a key role in the deNOx of ZrO2 -WO3 . Abstract: The catalyst for selective catalytic reduction of NOx at high temperatures is significantly demanded by current gas-fired exhaust purification. In this work, the complex oxides composed of two different structures of ZrO2 -WO3 and WO3 /ZrO2 with zirconium as the main component were prepared for NH3 -SCR of NO at high temperatures by blending method and equal volume impregnation method, respectively. Combined with XRD, NH3 -TPD, FE-SEM, BET and in situ DRIFTS characterization, the effects of component optimization of two kinds of ZrO2 and WO3 complex oxides on the performance for NH3 -SCR of NO were mainly studied. The optimal compatibility of ZrO2 and WO3 complex oxides was determined, and the corresponding N2 selectivity and anti-interference ability of water vapor and SO2 were further investigated. Results showed that the performance of ZrO2 -WO3 prepared by blending method for NH3 -SCR of NO was significantly better than that of WO3 /ZrO2 prepared by impregnation method. The ZrO2 -WO3 containing 20% WO3 has the best performance in NH3 -SCR of NO with NO conversion higher than 90% and N2 selectivity higher than 90% at 450–650 °C, and the performance was not affected by SO2, slightly affected by competitive adsorption of water vapor at 450 °C and not disturbed by water vapor above 500 °C. Further investigation showed that the NH3 -SCR of NO over the ZrO2 -WO3 reaction followed both L-H and E-R mechanisms. Characterization analysis revealed that ZrO2 -WO3 has finer microscopic particles, larger specific surface area, higher acid amount and stronger acid strength than WO3 /ZrO2 .